THE INFLUENCE OF BRAND IMAGE AND PRICE TOWARDS CAR PURCHASING DECISIONS AT LIEK MOTOR INDRAPURA SURABAYA - Dicky Esanata Soedarjanto; Is Fadhilah (Suluh Adiluhung Publisher (SAPub), 2024)
Determining a brand of product that consumers will choose is one of the influences towards consumer purchasing decisions in choosing that product. This research aims to determine the influence of brand image and price on the decision to purchase a Toyota car at PT. Liek Motor Indrapura Surabaya. The type of research used is quantitative research carried out by filling out questionnaires by consumers. The research results show that partially brand image and price have a positive effect on consumer purchasing decisions for Toyota cars at PT. Liek Motor Indrapura Surabaya. The better the brand image, the higher the consumer's purchasing decisions and vice versa. This means that the higher the car unit price, the lower the consumer purchasing decision and vice versa.